PENGARUH SOCIAL COMPARISON TERHADAP ENVY DAN NIAT MENGUNJUNGI DESTINASI WISATA DI INSTAGRAM - Edo Galih Permadi; Waras Waras (STIE Mahardhika, 2023)
Social media has become a place to share experiences when visiting tourist destinations. This research focuses on a phenomenon that is often experienced by Instagram social media users, namely comparing themselves with friends who uploaded interesting travel experiences and feeling envious. The data used in this study are 100 Instagram users who meet the criteria. Data collection was carried out by distributing questionnaires online. The results of the study shows that Instagram users who are involved in social comparisons, especially upward social comparisons, can feel envy, which creates an intention to visit tourist destinations uploaded by friends. Upward social comparison also directly influences the intention to visit tourist destinations. The theoretical implications of this study explains the mechanism in the relationship between social comparison, envy and the intention to visit tourist destinations. This research also explains the managerial implications that are useful in developing marketing strategies on social media.